2009
DOI: 10.1017/s0317167100006594
|View full text |Cite
|
Sign up to set email alerts
|

Precentral Knob Corresponds to the Primary Motor and Premotor Area

Abstract: Identification of the primary motor area (M1) using computerized tomography (CT) or magnetic resonance imaging (MRI) is critical to delineate the effect of various diseases (e.g., brain tumors, infarction, multiple sclerosis) as well as for the preoperative planning for patients undergoing resection of brain tumors. The utility of non-invasive identification of M1 using functional MRI (fMRI) has been demonstrated by comparing the location of M1 detected by fMRI with that by invasive and direct methods, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…7,20,48,55 For example, the concept of the precentral knob representing the primary motor area of the hand has In this "average brain," patients' brains were linearly transformed into a common space using a 12-parameter affine transformation.…”
Section: Intrinsic Functional Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…7,20,48,55 For example, the concept of the precentral knob representing the primary motor area of the hand has In this "average brain," patients' brains were linearly transformed into a common space using a 12-parameter affine transformation.…”
Section: Intrinsic Functional Variabilitymentioning
confidence: 99%
“…48 Others have reported variability in the functional organization of the primary sensorimotor cortices as well. For example, within the precentral gyrus, stimulation of individual cortical sites has been shown to recruit both sensory and motor phenomenon and in other cases stimulation has been shown to recruit motor movements in more than 1 motor group.…”
Section: Intrinsic Functional Variabilitymentioning
confidence: 99%
“…1). 22 While other investigators have reported that the electrophysiological method of SEP can localise the M1, 28 our studies demonstrated that the M1 was successfully localised by SEP in only 6 of 16 patients with brain tumours involving the M1 (Table II). Thus, neither the inverted omega method nor SEP can reliably localise the M1 in all cases.…”
Section: Localisation Of M1 In Patients With Brain Tumour Involving Tmentioning
confidence: 52%
“…Thus, neither the inverted omega method nor SEP can reliably localise the M1 in all cases. 14,22 Removal of brain tumour involving the M1 without induction of new motor deficits In our series of patients undergoing awake surgery for resection of brain tumours involving the M1 study, slight deficits in postoperative motor function occurred in 4 of 21 cases (Table II). By contrast, transient deterioration of either upper or lower limb motor function was observed in 13 of 21 cases during the awake surgery itself (Table II).…”
Section: Localisation Of M1 In Patients With Brain Tumour Involving Tmentioning
confidence: 85%
See 1 more Smart Citation